UJI TOKSISITAS DAN IDENTIFIKASI SENYAWA EKSTRAK ALGA MERAH (Eucheuma cottonii) TERHADAP LARVA UDANG Artemia salina LEACH - Sharo, Noer Mardlatillah; Ningsih, Rachmawati; Hanapi, Ahmad; Nasichuddin, Ahmad (ALCHEMY, 2013)
Eucheuma cottonii is a multicellular algae (multicellular) that have bioactive compounds used in medicine, such as anticancer. The purpose of this research is to know the level of toxicity of the crude extract of ethanol and n-hexane red algae (Eucheuma cottonii) against larvae of shrimp A. salina Leach and to know the active compounds contained in crude extracts of ethanol and n-hexane red algae (Eucheuma cottonii).This research was conducted with the maceration extraction continuing by test toxicity against the shrimp larvae of A. salina Leach (BSLT). The result of the toxicity test then proceeds with the test reagents and phytochemicals with thin layer chromatography for positive test of compound phytochemicals. Thin-layer chromatography using eluen n-hexane: ethyl acetate (7: 3) to ethanol extract and n-hexane: ethyl acetate (17: 3) for n-hexane extract. Data on toxicity of A. salina Leach analyzed by probit analysis to find out the value of LC50 on each extract.The results of this research indicate that each of the rough red algae extract (Eucheuma cottonii) by using a solvent of ethanol and n-hexane have toxicity values (LC50) of shrimp larvae of A. salina Leach consecutive 58,0128 ppm and 61,7571 ppm. Active compounds content of Phytochemical test results i.e. triterpenoid (ethanol extract) and steroids (n-hexsane extract). The TLC triterpenoid obtained 7 stains, and the results obtained steroids 8 TLC stains.